Context matters: Successes and challenges of intrapartum care scale-up in four districts of Afghanistan. Issue 4 (20th April 2016) - Tappis, Hannah; Koblinsky, Marge; Winch, Peter J.; Turkmani, Sabera; Bartlett, Linda
ABSTRACT: Reducing preventable maternal mortality and achieving Sustainable Development Goal targets for 2030 will require increased investment in improving access to quality health services in fragile and conflict-affected states. This study explores the conditions that affect availability and utilisation of intrapartum care services in four districts of Afghanistan where mortality studies were conducted in 2002 and 2011. Information on changes in each district was collected through interviews with community members; service providers; and district, provincial and national officials. This information was then triangulated with programme and policy documentation to identify factors that affect the coverage of safe delivery and emergency obstetric care services. Comparison of barriers to maternal health service coverage across the four districts highlights the complexities of national health policy planning and resource allocation in Afghanistan, and provides examples of the types of challenges that must be addressed to extend the reach of life-saving maternal health interventions to women in fragile and conflict-affected states. Findings suggest that improvements in service coverage must be measured at a sub-national level, and context-specific service delivery models may be needed to effectively scale up intrapartum care services in extremely remote or insecure settings.